Análise do risco fiscal da dívida pública nos estados brasileiros pelo exame do comportamento das despesas orçamentárias no período de 2008 a 2016 - Sá Filho, Clovis Soares e (2020)
The management of fiscal risks is seen as a necessary factor for the control of public debt and, consequently, for sustainable development. However, despite its importance being highlighted in international institutions (IMF, World Bank, OECD) and national (IPEA, TCU, STN), it has been difficult to develop it systematically and continuously in the context of brazilian states. This exploratory study investigates the relationship between public debt and budget expenditure accounts. It also suggests a model that can be used to monitor fiscal risks, through monitoring budget accounts, to identify the relationship between changes in expenses with the level of indebtedness. First, was presented a descriptive analysis of the states' indebtedness index and the predictive variables, the expense group accounts. Then, a classification with the Naive Bayes algorithm was estimated to assess the accuracy of the expense group accounts in identifying the level of the debt indicator. The results confirm this possibility of classifying debt based on the observation of the percentage structure of expenses over a total expenditure.